1983
DOI: 10.1007/bf00129432
|View full text |Cite
|
Sign up to set email alerts
|

Information theory methods for the study of spatial processes and succession

Abstract: The use of mathematical methods based on Shannon's entropy function is proposed for the evaluation of the consequences of sampling unit size and for the study of vegetation succession. The concept of diversity is extended to sets of phytosociological relev6s under the term florula diversity. It is shown that Shannon's entropy as well as two other related characteristic functions can express the local behaviour and overall relationships of species. Characteristic areas are defined in terms of the maxima and min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 20 publications
3
63
0
2
Order By: Relevance
“…This trend is consistent with findings of previous studies (Juhász-Nagy and Podani, 1983;Bartha, 1991;Tóthmérész, 1994;Bartha, 2001) and suggests a general pattern typical in regeneration process (Bartha, 2001(Bartha, , 2004, while the opposite trend is found in degradation (Bartha, 2001(Bartha, , 2004. Based on these results, beta diversity is an appropriate indicator for detecting recovery (assembly) or degradation (disassembly) in vegetation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This trend is consistent with findings of previous studies (Juhász-Nagy and Podani, 1983;Bartha, 1991;Tóthmérész, 1994;Bartha, 2001) and suggests a general pattern typical in regeneration process (Bartha, 2001(Bartha, , 2004, while the opposite trend is found in degradation (Bartha, 2001(Bartha, , 2004. Based on these results, beta diversity is an appropriate indicator for detecting recovery (assembly) or degradation (disassembly) in vegetation.…”
Section: Discussionsupporting
confidence: 91%
“…Beta diversity depends on spatial scale and on the abundance of species. The advantage of using Juhász-Nagy's models is the sigma additivity of models and the advanced methodology dealing with various aspects of scale dependence (Juhász-Nagy, 1980;Juhász-Nagy and Podani, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Starting from a homogeneous data set, the proposed case studies proved that the choice of the resolution scale affects the comprehension of the patterns of space occupancy and occurrence of the Habitats and the correlations between Habitats and environment (Greig-Smith, 1983;Juhász-Nagy & Podani, 1983;Reed, Peet, Palmer, & White, 1993), with a substantial relapse on the measurement of their AOO.…”
Section: Discussion: Lessons Learned and Perspectivesmentioning
confidence: 99%
“…Therefore, we decided to use beta diversity for measuring the effect of yellow bluestem. Our preliminary studies showed that within-community patterns of species composition were good indicators of grassland succession and degradation [13,[30][31][32]. In addition to be a good indicator, beta diversity reflects important constraints of the spatial organization of vegetation [31,33,34].…”
Section: Introductionmentioning
confidence: 99%